Physicochemical Characterization and Antibacterial Efficacy of Toothpaste Formulations Containing Arabica Coffee Husk Ethanol Extract Against Streptococcus mutans and Staphylococcus aureus - Natanael Priltius; Raissa Fitri; Novi Anisyah Fitrianty; Tristan Halawa; Adiansyah Adiansyah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Coffee husk, a major by-product of the coffee industry, is rich in phenolics, chlorogenic acid, and caffeine with known antioxidant and antimicrobial activities. This study evaluated Arabica coffee husk extract as an active ingredient in herbal toothpaste formulations, focusing on stability and antibacterial efficacy. Oral health problems, particularly dental caries, remain a global concern, affecting 2.3 billion people in permanent teeth and over 530 million children in primary teeth. Streptococcus mutans is the main cariogenic bacterium, while Staphylococcus aureus also contributes to oral infections. Safe, effective, and natural antimicrobial agents are urgently needed for prevention. Methodology: Arabica coffee husk powder was characterized Physicochemical according to the Indonesian Materia Medica (MMI). Toothpaste formulations containing 1%, 3%, and 5% w/w ethanol extract were prepared and tested for organoleptic properties, homogeneity, and stability over three weeks at room temperature. Stability was assessed weekly by monitoring pH, viscosity, temperature, phase separation, and color changes. Antibacterial activity against S. mutans and S. aureus was evaluated using the agar well diffusion method. All treatment were conducted in triplicate (n = 3). Findings: Phytochemical evaluation confirmed compliance with MMI standards. All formulations remained stable in color, odor, and consistency, with no phase separation or microbial contamination. Antibacterial assays showed concentration-dependent inhibition:  the 5% extract (F3) produced inhibition zones of 18.2 ± 0.5 mm against S. mutans and  15.6 ± 0.7 mm against S. aureus. The negative control (without extract) showed no inhibition, while the positive control (chlorhexidine) produced clear zones. Contribution: Arabica coffee husk extract can be formulated into stable toothpaste with significant antibacterial activity, particularly against S. mutans, supporting its potential as a sustainable natural oral care agent